Evaluating Kidney Function Decline in Children with Chronic Kidney Disease Using a Multi-Institutional Electronic Health Record Database. Issue 2 (18th February 2023) - Gluck, Caroline A.; Forrest, Christopher B.; Davies, Amy Goodwin; Maltenfort, Mitchell; Mcdonald, Jill R.; Mitsnefes, Mark; Dharnidharka, Vikas R.; Dixon, Bradley P.; Flynn, Joseph T.; Somers, Michael J.; Smoyer, William E.; Neu, Alicia; et al.
Visual Abstract: Abstract : Background: The objectives of this study were to use electronic health record data from a US national multicenter pediatric network to identify a large cohort of children with CKD, evaluate CKD progression, and examine clinical risk factors for kidney function decline. Methods: This retrospective cohort study identified children seen between January 1, 2009, to February 28, 2022. Data were from six pediatric health systems in PEDSnet. We identified children aged 18 months to 18 years who met criteria for CKD: two eGFR values <90 and ≥15 ml/min per 1.73 m 2 separated by ≥90 days without an intervening value ≥90. CKD progression was defined as a composite outcome: eGFR <15 ml/min per 1.73 m 2, ≥50% eGFR decline, long-term dialysis, or kidney transplant. Subcohorts were defined based on CKD etiology: glomerular, nonglomerular, or malignancy. We assessed the association of hypertension (≥2 visits with hypertension diagnosis code) and proteinuria (≥1 urinalysis with ≥1+ protein) within 2 years of cohort entrance on the composite outcome. Results: Among 7, 148, 875 children, we identified 11, 240 (15.7 per 10, 000) with CKD (median age 11 years, 50% female). The median follow-up was 5.1 (interquartile range 2.8–8.3) years, the median initial eGFR was 75.3 (interquartile range 61–83) ml/min per 1.73 m 2, 37% had proteinuria, and 35% had hypertension. The following were associated with CKD progression: lower eGFR category (adjusted hazard ratio [aHR] 1.44 [95% confidence interval (95% CI), 1.23 to 1.69], aHR 2.38 [95% CI, 2.02 to 2.79], aHR 5.75 [95% CI, 5.05 to 6.55] for eGFR 45–59 ml/min per 1.73 m 2, 30–44 ml/min per 1.73 m 2, 15–29 ml/min per 1.73 m 2 at cohort entrance, respectively, when compared with eGFR 60–89 ml/min per 1.73 m 2 ), glomerular disease (aHR 2.01 [95% CI, 1.78 to 2.28]), malignancy (aHR 1.79 [95% CI, 1.52 to 2.11]), proteinuria (aHR 2.23 [95% CI, 1.89 to 2.62]), hypertension (aHR 1.49 [95% CI, 1.22 to 1.82]), proteinuria and hypertension together (aHR 3.98 [95% CI, 3.40 to 4.68]), count of complex chronic comorbidities (aHR 1.07 [95% CI, 1.05 to 1.10] per additional comorbid body system), male sex (aHR 1.16 [95% CI, 1.05 to 1.28]), and younger age at cohort entrance (aHR 0.95 [95% CI, 0.94 to 0.96] per year older). Conclusions: In large-scale real-world data for children with CKD, disease etiology, albuminuria, hypertension, age, male sex, lower eGFR, and greater medical complexity at start of follow-up were associated with more rapid decline in kidney function.